Evaluating Digital Inclusion Policy in Local Civil Registration Services: A Case Study of North Kolaka Regency - A. Khusnul Khatimah; Nuryanti Mustari; Ihyani Malik (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
Digital inclusion policies in public services aim to bridge the digital divide and ensure equitable access to government administrative systems. This study evaluates the effectiveness of the digital inclusion policy implemented through the "Si Laku O2T" (Sistem Layanan Adminduk Kolaka Utara Offline, Online, dan Terintegrasi) innovation program at the Department of Population and Civil Registration of North Kolaka Regency. Using a qualitative descriptive research design, data were gathered through semi-structured interviews with policy implementers, civil servants, and community members, alongside direct field observations and comprehensive document analysis. The evaluation framework was based on William N. Dunn’s policy evaluation metrics: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that while "Si Laku O2T" has significantly enhanced administrative efficiency and simplified document issuance through its integrated and mobile-based services (such as "La Jebola"), full policy effectiveness is still constrained by structural barriers. These limitations include unstable telecommunication networks in remote mountainous areas, inadequate digital literacy among rural populations, and the lack of standardized digital infrastructure at the village level. Consequently, while the program represents a major step forward in administrative modernization, its transformative potential is unevenly distributed. This study recommends prioritizing local network infrastructure expansion, conducting sustained community digital literacy training, and standardizing administrative support systems across rural jurisdictions.